Sleep duration and dietary macronutrient consumption can modify the cardiovascular disease for Korean women but not for men. Issue 1 (December 2016) - Doo, Miae; Kim, Yangha
Abstract Background Although the association between cardiovascular disease (CVD) and sleep duration is generally recognized, the results are inconsistent, and investigations examining the effects of seep duration and diet on CVD are rare. Methods The gender-difference in the effect of the sleep duration on Framingham risk score (FRS)-related factors, 10‐year predicted CVD risk, and dietary consumption was analyzed in 14, 111 subjects (Menn = 5, 727; Womenn = 8, 384) aged ≥20 from the Korean National Health and Nutrition Examination Survey. Results The gender difference in the CVD risk factors according to sleep duration was observed. Only women with short sleep durations (<7 h/day) exhibited elevated FRS factors, such as systolic blood pressures (SBP) (P < 0.001), diastolic blood pressures (DBP) (P = 0.008), and the proportion of hypertension (HTN) treatments (P < 0.001), but not for men. Moreover, the 10-year predicted CVD risk, as evaluated with the FRS, was higher in women with short sleep durations (P < 0.001). Women with short sleep durations consumed significantly more dietary carbohydrates (CHO) than those with normal sleep durations (P < 0.001). Additionally, the ORs for intermediate and high 10-year predicted CVD risks and CVD–related factors, such as high age, elevated SBP, and HTN treatment, significantly increased with short sleep durations among women [OR (95 % CI) = 1.709 (1.359–2.149) for CVD risk, 1.976 (1.756–2.224) for high age, 1.535 (1.291–1.826) for elevated SBP, and 1.515 (1.320–1.739) for HTN treatment]. Conclusions Short sleep duration influenced dietary carbohydrate consumption and elevated FRS-related factors as well as 10-year predicted CVD risk. Our findings demonstrated that the CVD risk has been potentially modified by short sleep durations and greater CHO consumptions.